THE EFFECTIVENESS OF TEACHING VOCABULARY BY USING CONTEXTUAL SENTENCES - Farikha, Ninik (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2024)
The aim of this research is to describe the teaching vocabulary by using contextual sentences for the students of Sibling English Course. The methodology used is quantitative research design with 24 samples of students. This research researcher conducted two tests to get the data, the tests are (1) pre-test to know students’ basic ability in writing and (2) post-test to know students’ vocabulary ability after giving treatment. In doing treatment the researcher used describing contextual sentences as technique in teaching vocabulary. The result of this research is found that the mean score of pre-test was 58.75 and the mean of post-test was 70.42. From both of the data it was found that the result of post-test was higher than the result of pre-test. Then statistically, the data got was analyzed by using SPSS 15.0 version to find t-test. From the computation of the data it was found that the t-test was higher than t-table in significant level 1% and 5 % (2,07<4,049>2,81). From the result of this research showed that contextual sentences are effective in teaching vocabulary of Sibling English Course.